Penanaman Karakter Islami Di SMP Muhammadiyah 1 Gatak Sukoharjo Tahun 2015 - PURWANTO, Purwanto (2016)
The Cultivation of Islamic Characters in SMP Muhammadiyah 1 Gatak Sukoharjo in 2015. The objective of this research is to describe the Islamic characters cultivated in SMP Muhammadiyah 1 Gatak Sukoharjo. Which methods used in cultivating the Islamic characters in SMP Muhammadiyah 1 Gatak Sukoharjo are. What supporting and inhibiting factors in the cultivation of the Islamic character in SMP Muhammadiyah 1 Gatak Sukoharjo are. Kind of this research is a field research with an ethnographic approach. The research location is in SMP Muhammadiyah 1 Gatak Sukoharjo. The techniques of data collection are through interview, observation, and documentation. Meanwhile, the analysis is conducted through data collection, data reduction, data display, and conclusion drawing. The results of the research on the character values cultivated in SMP Muhammadiyah 1 Gatak in 2015 are as follows: piety, sincerity, gratefulness, trust in and reliance on God, repentance, loving and honoring Rasulullah (Prophet Muhammad) saw, following and obeying Rasulullah saw, reciting shalawat and greeting to Rasulullah saw, shiddiq (being correct), tawadhu' (being humble), amanah (being trustworthy), syaja'ah (being brave based on truth), being bashful, birrul walidain (being a dutiful child for parents), keeping fraternity, amar makruf nahi munkar (enjoining good and forbidding wrongdoing). The methods used in cultivating the Islamic character in SMP Muhammadiyah 1 Gatak in 2015 are as follows: good modelling, targhib and tarhib (targhib is a method in education by conveying good news/hope to the students orally or in written in order that the students become pious men, in contrary, tarhib uses bad news/threat to the students for the similar goal), habituation, order and prohibition, as well as story and guidance. The supporting factors are: the headmaster's role, the amount of students (not-too-many amount), family that cares moral education, and good environment. The inhibiting factors are: family that does not care moral education much, bad environment, social media and internet, togetherness of all teachers in building the students' moral, and the students' activeness in the school activities. Keywords: Cultivation, Character, and Islamic.